'All that Glisters': Orpheus's Failure as an Orator and the Academic Philosophy of the Accademia degli Invaghiti. (13th October 2014) - Schwindt, Joel
Abstract Scholarship on Monteverdi's Orfeo has frequently considered Orpheus's failure to persuade Charon during his grand aria-oration, 'Possente spirto', in terms of style and performance. In the eyes of academics such as the Accademia degli Invaghiti (for whom Orfeo was first composed), however, these issues would have been viewed as secondary to the goal of offering moral instruction, in keeping with the Ciceronian maxim, 'instruction is the first goal, followed by the movement of the mind, and the delight of the senses'. After assessing the compatibility of my 'academic' reading of Orfeo with those that have focused on the subject of music and its power, this article considers the Invaghiti's practice and philosophy of oratory, as well as Monteverdi's knowledge of this art. The reasons for Orpheus's failure as an orator are then considered through a comparative analysis of 'Possente spirto' and the other full oration from Orfeo, La Musica's Prologue, as well as further 'musical orations' from Monteverdi's catalogue. This analysis is based primarily on the teachings of the Ancients, as interpreted in the writings of Academy member Stefano Guazzo – in particular his dialectic on 'civil conversation' – as well as the model presented in academy member Pompeo Baccusi's oration, 'In defence and praise of women', given for the Invaghiti in 1571.